MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL KOOPERATIF TIPE SNOWBALL THROWING PADA TEMA 7 - Ayu Daniati Manurung; Ester Julinda Simarmata; Dewi Anzelina; Darinda Sofia Tanjung (JS (JURNAL SEKOLAH), 2023)
Abstrct: This This study aims to determine student learning outcomes by applying the Snowball Throwing cooperative learning model with the theme of the beauty of diversity in my country in grade IV SD Negeri 060935 Kec. Medan Johor Academic Year 2021/2022. The subjects of this study were 24 students consisting of 10 female students and 14 male students. The technique used by researchers in collecting data used in this study is observation and tests. The learning model used in this study is a cooperative model of snowball throwing type. The results of this study indicate an increase in student learning outcomes with the theme of the beauty of diversity in my country in grade IV SD Negeri 060935 Kec. Medan Johor. This is evident from the results of his research conducted at the time of the pretest that has completeness with an average student learning outcome of 52.98. In the posttest cycle I the average learning outcome was 78.40%, then the second cycle there was an increase in student learning outcomes with an average of 86.33%. Thus, it was concluded that by using the Snowball Throwing Cooperative learning model, there was an increase in student learning outcomes on the theme of the Beauty of Diversity in My Country in Grade IV SD Negeri 060935 Kec. Medan Johor Academic Year 2021/2022. Keywords: Learning Outcomes, Snowball Throwing Abstrak: Penelitian ini bertujuan untuk mengetahui hasil belajar siswa dengan menerapkan model pembelajaran kooperatif Snowball Throwing dengan Tema Indahnya Keberagaman di Negeriku di kelas IV SD Negeri 060935 Kec. Medan Johor Tahun Pembelajaran 2021/2022. Subjek penelitian ini adalah 24 siswa yang terdiri dari 10 siswa perempuan dan 14 siswa lai-laki. Teknik yang digunakan oleh peneliti dalam mengumpulkan data yang digunakan dalam penelitian ini adalah observasi dan tes. Model pembelajaran yang dugunakan dalam penelitian ini adalah model kooperatif tipe snowball throwing. Hasil penelitian ini menunjukkan adanya peningkatan hasil belajar siswa dengan Tema Indahnya Keberagaman di Negeriku di kelas IV SD Negeri 060935 Kec. Medan Johor. Hal ini terbukti dari hasil penelitiannya yang dilakukan pada saat pretest memiliki ketuntasan dengan rata-rata hasil belajar siswa . Pada postes siklus I rata-rata hasil belajar 78,40%, kemudian siklus II terjadi peningkatan hasil belajar siswa dengan rata-rata 86,33%. Dangan demikian, diperoleh kesimpulan bahwa dengan menggunakan model pemebelajaran Kooperatif Tipe Snowball Throwing terjadi peningkatan terhadap hasil belajar siswa pada tema Indahnya Keberagaman di Negeriku di Kelas IV SD Negeri 060935 Kec. Medan Johor Tahun Pembelajaran 2021/2022. Kata Kunci: Hasil Belajar, Snowball Throwing